Temperature-sensitive hydrogels by graft polymerization of chitosan and N-isopropylacrylamide for drug release. (October 2013) - Spizzirri, Umile Gianfranco; Iemma, Francesca; Cirillo, Giuseppe; Altimari, Ilaria; Puoci, Francesco; Picci, Nevio
<x xml:space="preserve">Abstract</x> Thermo-responsive polysaccharidic hydrogels were designed and synthesized by a free radical induced grafting procedure. Chitosan was chosen as biopolymer to impart biocompatibility and biodegradability to the macromolecular systems, while N-isopropylacrylamide (NIPAAm) was selected as co-monomer responsive for the thermo-sensitive properties. Ammonium persulfate was the initiator system and different polymeric networks have been synthesized by modulating the amount of NIPAAm in the polymerization feed. The resulting hydrogels were proposed as drug delivery devices and their performance was evaluated by using Diclofenac sodium salt as a model drug. Hydrogels were carefully characterized by FT-IR spectrophotometry, calorimetric analyses and swelling behavior in a temperature range of 15–45°C. Finally, to verify the suitability of these hydrogels as thermo-responsive devices, the drug release profiles were studied performing in vitro experiments around the swelling-shrinking transition temperatures of the macromolecular systems.